Identification of the Inrush Current of the Internal Faults of Power Transformers Based on the Differential Relay Function - Majid Salimi (International Journal of Advances in Applied Sciences, 2016)
The inrush current of transformer is one of the most important factors in the damaging of power transformers and reducing their useful life. Differential relays are one of the main and primary protections of power transformers. Therefore, the correct and fast operation of these devices is so important. In this paper, an inrush flow detection method is proposed in order to prevent the inaccurate performance of differential relay. In the proposed method, the analysis of the wavelet transform frequency time is used based on the extracted characteristics. Also, a criterion called correlation coefficient is used in order to create a suitable pattern and use it in the proposed algorithm. The simulation of the proposed algorithm is performed by the PSCAD software and implemented in the MATLAB environment. The results of the simulation confirm the accuracy of the proposed method.